THE CONTRIBUTION OF APPLIED PSYCHOLOGY FOR EDUCATIONAL MANAGEMENT ISSUE - Ivan Riyadi (Psychosophia: Journal of Psychology, Religion, and Humanity, 2020)
This article discusses education management in frame psychology. The education management is a factual behavior of the psychological discipline that is depicted in through the analysis of the behavior system of the school organization involving a number of components. In the application of psychology in education management is a part of the element that is not stuck in the view of uniformity that practically diversity by each education leadership. Each educational institution is a singularity that relates to the differences in the nature and condition of each component of the psychological system. To get an intact picture in this article, then used a qualitative approach with literature research design. The results of the study indicated that such an understanding is to be aware of educational practitioners of the importance of psychology universally, through culture, and psychology and social. Then the role of education management is very important especially educational institutions tailored to the psychological conditions of managerial and the needs of students.